Effects of Militancy Activities on Secondary School Students’ Dropout in the Niger Delta Region. - Igwela, J. N.; Amie-Ogan, O. T.; Osuji, C. U. (Journal of Education and Practice, 2022)
Purpose: This study examines how the militancy activities (attacks, hostility, unfairness and victimization) in the Niger Delta Region of Nigeria influenced secondary school students' dropout (SSSD) and the implications for educational development. Methodology: The research design adopted was descriptive survey design using the cross-sectional data from 904 students of 30 public secondary schools located in the communities with high militancy activities in three of the nine Niger Delta states. The direct influence of the outcomes of militancy activities on SSSD were tested using hierarchical regression. Results: The results show that the outcomes of militancy activities were associated positively with SSSD, indicating that the outcomes of the militancy activities significantly influence SSSD in the study population. The present study contributes to knowledge and extends research on the effects of the militancy activities on secondary school students' dropout and enrolment in school programmes. Unique Contribution to Theory, Policy and Practice: The findings have practical and policy implications for educational development in the Niger Delta region. Based on the findings, the study recommended among others that government should create employment opportunities for the youths.